The Impact of body dissatisfaction on distressing sexual difficulties among men and women: The mediator role of cognitive distraction - Carvalheira, Ana (2017)
Research has demonstrated a negative impact of cognitive distraction on sexual activity, and body dissatisfaction has been associated with less satisfying and fewer sexual activities. In the current study we examined the extent to which cognitive distraction, based on body appearance and sexual performance, mediated the impact of body dissatisfaction on sexual difficulties among women and men. A sample of 493 women (Mage = 30.61) and 595 men (Mage = 37.90) completed an online survey. Women reported significantly higher levels of distressing sexual difficulties, significantly more body dissatisfaction, and greater cognitive distraction based on appearance than men. In contrast, men reported higher cognitive distraction based on performance than women. A path analysis model indicated that, for men, only cognitive distraction based on performance mediated the effects of body dissatisfaction on distressing sexual difficulties, and the mediation was only partial as body dissatisfaction had a significant direct effect on distressing sexual difficulties. In contrast, among women, both appearance-based cognitive distraction and performance-based cognitive distraction fully mediated the effects of body dissatisfaction on distressing sexual difficulties.